Compromised quality of maternal healthcare in a market economy: Medellín, Colombia 2008-2009 (2011)
ABSTRACT: Objective: To analyze the quality of the maternal health services in Medellín city, Colombia within the context of the Socia Security System in Health from the perspective of the mothers, physicians and nurses involved in the provision of these services. Methodology: A qualitative study was carried out, during which 24 individual interviews were conducted to key doctors and nurses, who work in health institutions that providing maternal care. Also three focus groups with mothers were conducted. The data analysis was carried out using a systematic and carefully coding and categorization process. Findings:In spite of the fact that municipal policies have been put in place to improve maternity care, mother and pregnant women face problems with health services. Findings suggests that the strategies put in place by these health institutions to decrease labor costs, the administrative barriers, the low tariffs of the obstetric services paid by the health insurers within and competitive market, and the focus on getting financial profitability, are aspects that affecting quality of maternal care.